2014
DOI: 10.1155/2014/709691
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum Uric Acid and Residualβ-Cell Function in Type 2 Diabetes

Abstract: The aim of this study was to investigate the relationship of serum uric acid (sUA) with residual β-cell function in type 2 diabetes. Oral glucose tolerance tests (OGTT) were performed on 1021 type 2 diabetes patients. The ratio of area under curve of insulin to glucose during 0 to 30 min and 0 to 120 min of the OGTT was calculated as indices of insulin secretion function. The products of insulin secretion indices multiplied by Matsuda insulin sensitivity index were used as disposition indices. After correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 33 publications
2
38
1
Order By: Relevance
“…Although several studies showed that BMI, hypertension, and uric acid serum were associated with composition of stone formation 2,24,26 our study showed no statistically significant associations.…”
Section: Discussioncontrasting
confidence: 90%
“…Although several studies showed that BMI, hypertension, and uric acid serum were associated with composition of stone formation 2,24,26 our study showed no statistically significant associations.…”
Section: Discussioncontrasting
confidence: 90%
“…Although most clinical studies revealed a positive correlation between SUA level and islet β‐cell function in patients with T2DM, the correlation is still controversial. Mechanism researches show that SUA suppresses basal insulin release in isolated rat pancreatic islets and inhibits glucose‐stimulated insulin secretion .…”
Section: Discussionmentioning
confidence: 99%
“…The association between SUA and abnormal insulin secretion was also reported in subjects with normal or impaired glucose metabolism. A study conducted by Tang et al showed that patients with higher SUA have greater insulin secretion ability than those with lower SUA at the early stage of disease, but their residual β‐cell function seems to decay more rapidly . A positive relationship between SUA and total phase of insulin secretion among T2DM adults was also demonstrated by Robles by using hyperglycemia clamp technique .…”
Section: Introductionmentioning
confidence: 88%
“…Robles‐Cervantes et al reported that uric acid concentration had a positive relationship with insulin secretion, which may play an important role in the function of β‐cell in patients with T2DM. Tang et al reported that subjects with higher uric acid concentration have greater insulin secretion ability than those with lower uric acid at the early stage of T2DM, but their residual β‐cell function seems to decay more rapidly.…”
Section: Discussionmentioning
confidence: 99%